THE EFFECT OF SEASONAL CHANGE ON THE ANTIBACTERIAL ACTIVITY OF C. EDULIS - Chokoe, P. K.; Masoko, P.; Mokgotho, M. P.; Howard, R. L.; Mampuru, L. J. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Carpobrotus edulis (family Aizoaceae) has been used over the years to treat microbial infections. Previously, the antibacterial activity of the plant had only been qualitatively assessed. The antibacterial activity of the plant harvested during different times of the year was quantitatively evaluated by preparing extracts of varying polarities from the leaf debris and filtrate of a Spring and an Autumn harvest of C. edulis. Thin layer chromatography was used to analyze the phytocompounds of the extracts as well as to assay the plant for antioxidant compounds. The Spring harvest showed equal distribution of the phytochemicals within the leaf debris and the filtrate, but there was a high prevalence of phytocompounds within the leaf debris extracts of the Autumn sample. An antioxidant compound was intensely pronounced in the Autumn extracts of intermediate polarity and in the polar extract. The plant was evaluated for antibacterial activity against Escherichia coli, Enterococcus faecalis, Pseudomonas aeruginosa and Staphylococcus aureus by using a two-fold serial microdilution method as well as bioautography. Staphylococcus aureus was found to be the most sensitive bacterium to the plant extracts and P. aeruginosa was resistant to the extracts. The spring extracts were more potent against all test organisms, showing MIC values that were lower than those of the Autumn extracts. When taking the total activity of each extract into account, the autumn extracts showed higher efficacy than the extracts from the Spring sample. The antibacterial activity observed in extracts of both seasons somewhat validated the ethnomedicinal usage of C. edulis by traditional healers. Acknowledgements: University of Limpopo Senate Research Fund and National Research Foundation provided funding.